2018
DOI: 10.1155/2018/4923898
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Nonlinear Characteristics of a Rotating Flexible Blade with Dovetail Interface Feature

Abstract: A dynamic model is proposed in this paper for analyzing the nonlinear characteristics of a flexible blade. The dynamical equation of motion for a rotational flexible blade in a centrifugal force field is established based on the finite element method. A macro-stickslip mechanical model of dry friction is established to simulate the constraint condition of the flexible blade. The combined motion of the external excitation and friction produces a piecewise linear vibration which is actually nonlinear. The numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…e vibration responses of the developed model and FE model in Ref. [8] are presented and compared to further validate the derived mode function. In this paper, the Rayleigh damping is adopted, as introduced in Section 2.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…e vibration responses of the developed model and FE model in Ref. [8] are presented and compared to further validate the derived mode function. In this paper, the Rayleigh damping is adopted, as introduced in Section 2.…”
Section: Model Validationmentioning
confidence: 99%
“…Macroslip model and microslip model are two different kinds of friction mechanism model of friction damper. Macroslip model is extensively used firstly [6][7][8], which assumes that the contact DOF is in either slipping state or sticking state. en, a more realistic model is researched, which is microslip model [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Khaniki [20] concluded the disability of the nonlocal elastic theory differential form for presenting a reliable investigation on transverse vibrational behavior of rotating beams. Li et al [21] built their dynamic model based on the finite element method in order to analyze the nonlinear characteristics of a flexible blade contained in a centrifugal force field. Yao et al [22] investigated the varying-rotating-speed blade dynamic responses to the supersonic airflow and the cross-section warping effect.…”
Section: Introductionmentioning
confidence: 99%
“…As nonlinear characteristics are induced, blades will present nonlinear vibration responses. Li et al [18] established dry friction model for dovetail tenons and studied the effects on vibration response of blades under various rotating speeds, friction coefficients, and external force amplitudes. It is found that, in certain conditions, vibration responses of tenons include harmonics not only with the same frequency as excitation force but its 3x and 5x components.…”
Section: Introductionmentioning
confidence: 99%